2017
DOI: 10.1002/anie.201702171
|View full text |Cite
|
Sign up to set email alerts
|

Zinc–Zinc Double Bonds: A Theoretical Study

Abstract: While double bonds are known for transition metals of Groups 9 and 10 as well as for boron and p-block elements of Groups 14-16, Zn sits in a small region of the periodic table with no well-characterized double bonds. A qualitative reasoning indicates that zero-valent zinc has the potential to form Zn=Zn double bonds. A computational study in search for complexes that might showcase this new bond type is presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Figures and show the resulting optimized structures, whereas selected structural data for these complexes are collected in Tables and S1 (Supporting Information). The computed distances, reported by Alvarez and coworkers, for the double dizinc bond in [Zn 2 (L) 4 ] complexes are within the 2.27‐2.37 Å range. These lengths are shorter than 2.38 Å, the mean value of a ZnZn single bond found in experimental ZnZn complexes (range 2.29‐2.48 Å) .…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Figures and show the resulting optimized structures, whereas selected structural data for these complexes are collected in Tables and S1 (Supporting Information). The computed distances, reported by Alvarez and coworkers, for the double dizinc bond in [Zn 2 (L) 4 ] complexes are within the 2.27‐2.37 Å range. These lengths are shorter than 2.38 Å, the mean value of a ZnZn single bond found in experimental ZnZn complexes (range 2.29‐2.48 Å) .…”
Section: Resultsmentioning
confidence: 55%
“…[21-23] From a theoretical point of view, the most important recent finding is the possibility of a double bond between 2 zinc atoms, as has been recently demonstrated by Alvarez et al in several dizinc(0) complexes of general formula [Zn 2 (L) 4 ]. [24] These compounds can be isolobally related to olefins and diborenes taking into account that the [Zn(CO) 2 ] fragment could be considered to be isolobal with a CR 2 carbene. [24] Following our interest in the dizinc bond, [25] [Zn 2 (CO) 4 ] complex was selected as a representative example of a dizinc compound with a Zn Zn double bond.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is only one study discussed theoretically about the ZnÀ Zn multiple bond reported by Echeverría et.al. [25] In these Zn=Zn double bonded molecules, the Zn atom is sp 2 hybridized to accommodate the electrons from the π acid ligands like N-heterocyclic carbenes (NHCs) or CO. Since the degeneracy of π orbitals in Zn 2 fragment is destroyed, only the traditional double bond (one σ bond plus one π bond) is constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the 4p orbitals have been occupied by electrons among Zn=Zn double bonded molecules constructed by π acid ligands, Zn atom is still in zero oxidation state on account of the d-π* backdonation between the central Zn atom and the π acid ligands. [25] Therefore, we wonder whether can realize Zn=Zn double-π bond in one system and simultaneously Zn atom holds a negative oxidation state? To realize this expectation, not only the empty 4p orbitals of Zn atom should be occupied but also the degeneracy of π bonding orbitals must be maintained.…”
Section: Introductionmentioning
confidence: 99%